Ecological homogenization of soil properties in the American residential macrosystem. Issue 9 (6th September 2022) - Ryan, Christopher D.; Groffman, Peter M.; Grove, J. Morgan; Hall, Sharon J.; Heffernan, James B.; Hobbie, Sarah E.; Locke, Dexter H.; Morse, Jennifer L.; Neill, Christopher; Nelson, Kristen C.; O'Neil‐Dunne, Jarlath; Roy Chowdhury, Rinku; et al.
Abstract: The conversion of native ecosystems to residential ecosystems dominated by lawns has been a prevailing land‐use change in the United States over the past 70 years. Similar development patterns and management of residential ecosystems cause many characteristics of residential ecosystems to be more similar to each other across broad continental gradients than that of former native ecosystems. For instance, similar lawn management by irrigation and fertilizer applications has the potential to influence soil carbon (C) and nitrogen (N) pools and processes. We evaluated the mean and variability of total soil C and N stocks, potential net N mineralization and nitrification, soil nitrite (NO2 − )/nitrate (NO3 − ) and ammonium (NH4 + ) pools, microbial biomass C and N content, microbial respiration, bulk density, soil pH, and moisture content in residential lawns and native ecosystems in six metropolitan areas across a broad climatic gradient in the United States: Baltimore, MD (BAL); Boston, MA (BOS); Los Angeles, CA (LAX); Miami, FL (MIA); Minneapolis–St. Paul, MN (MSP); and Phoenix, AZ (PHX). We observed evidence of higher N cycling in lawn soils, including significant increases in soil NO2 − /NO3 −, microbial N pools, and potential net nitrification, and significant decreases in NH4 + pools. Self‐reported yard fertilizer application in the previous year was linked with increased NO2 − / NO3 − content and decreases in total soil N and C content. Self‐reported irrigation in the previous year was associated with decreases in potential net mineralization and potential net nitrification and with increases in bulk density and pH. Residential topsoil had higher total soil C than native topsoil, and microbial biomass C was markedly higher in residential topsoil in the two driest cities (LAX and PHX). Coefficients of variation for most biogeochemical metrics were higher in native soils than in residential soils across all cities, suggesting that residential development homogenizes soil properties and processes at the continental scale.